Engineering Enzyme Stability and Resistance to an Organic Cosolvent by Modification of Residues in the Access Tunnel1. Issue 7 (9th January 2013) - Koudelakova, Tana; Chaloupkova, Radka; Brezovsky, Jan; Prokop, Zbynek; Sebestova, Eva; Hesseler, Martin; Khabiri, Morteza; Plevaka, Maryia; Kulik, Daryna; Kuta Smatanova, Ivana; Rezacova, Pavlina; Ettrich, Rudiger; et al.
<x xml:space="preserve">Abstract</x> Mutations targeting as few as four residues lining the access tunnel extended the half‐life of an enzyme in 40 % dimethyl sulfoxide from minutes to weeks and increased its melting temperature by 19 °C. Protein crystallography and molecular dynamics revealed that the tunnel residue packing is a key determinant of protein stability and the active‐site accessibility for cosolvent molecules (red dots).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>